Application of Greimass semiotics in analysis of mathematical texts - Kudžma, Ričardas; Preidytė, Simona (Lietuvos matematikos rinkinys, 2013)
Nowadays one can see increase in analysis of mathematical textbooks. Even special conferences are running for this topic. Both authors of this article are taking part in Nordisk Network for research on mathematics textbooks in the Nordic countries. In this article semiotics of A.J. Greimas is being applied for analysis two mathematical texts about positive and negative numbers for grade 6 from different books. Analysis allows evaluate the quality of texts.